2017
DOI: 10.1038/s41598-017-16544-6
|View full text |Cite
|
Sign up to set email alerts
|

Associating a product with a luxury brand label modulates neural reward processing and favors choices in materialistic individuals

Abstract: The present study investigated the extent to which luxury vs. non-luxury brand labels (i.e., extrinsic cues) randomly assigned to items and preferences for these items impact choice, and how this impact may be moderated by materialistic tendencies (i.e., individual characteristics). The main objective was to investigate the neural correlates of abovementioned effects using functional magnetic resonance imaging. Behavioural results showed that the more materialistic people are, the more they choose and like ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 62 publications
2
5
0
2
Order By: Relevance
“…Notably, our results show how strong the impact of brand information may be to (materialistic) consumers, as the brands were randomly presented with products, but still lead to a preference for the respective products. This result, consistent with previous research (e.g., Audrin et al, 2017a , b ), points out that values are important factors to be taken into account when studying consumer decision-making. While the behavioral (choice variable) results revealed strong evidence in favor of our hypotheses, evidence was weaker regarding the eye-tracking data, which gave only moderate support to our hypotheses.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Notably, our results show how strong the impact of brand information may be to (materialistic) consumers, as the brands were randomly presented with products, but still lead to a preference for the respective products. This result, consistent with previous research (e.g., Audrin et al, 2017a , b ), points out that values are important factors to be taken into account when studying consumer decision-making. While the behavioral (choice variable) results revealed strong evidence in favor of our hypotheses, evidence was weaker regarding the eye-tracking data, which gave only moderate support to our hypotheses.…”
Section: Discussionsupporting
confidence: 92%
“…While the effect was not strong in our results regarding the pattern of visual attention, results on the choice variable revealed that the brand had a different impact on participants' choice, depending on their level of materialism. These results show further evidence that the brand was a strong vector of the luxury dimension of a product for materialistic people (Audrin et al, 2017a , b ). More generally, this result echoes previous results revealing the strong link between materialism and luxury (Gil et al, 2012 ).…”
Section: Methodssupporting
confidence: 73%
See 2 more Smart Citations
“…In the reward system, the caudate and anterior putamen play roles in reward expectation and the middle-posterior putamen coded values for habitual behaviors (Kawagoe et al, 1998 ; Gerardin et al, 2003 ; Haruno and Kawato, 2006 ; Balleine et al, 2007 ; Van Wouwe et al, 2012 ; Wunderlich et al, 2012 ; Lee et al, 2014 ). In addition, the caudate acts as an integrator in the brain valuation system that evaluates subjective values (Bartra et al, 2013 ; Audrin et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%